A Randomised Clinical Trial to Reduce Patient Prehospital Delay to Treatment in Acute Coronary Syndrome - Dracup, K.; McKinley, S.; Riegel, B.; Moser, D.; Meischke, H.; Doering, L.; Davidson, Patricia; Paul, Steven; Baker, H.; Pelter, M. (American Heart Association, 2009)
Background: Delay from onset of acute coronary syndrome (ACS) symptoms to hospital admission continues to be prolonged. To date, community education campaigns on the topic have had disappointing results. Therefore, we conducted a clinical randomised trial to test whether an intervention tailored specifically for patients with ACS and delivered one-on-one would reduce prehospital delay time. Methods and Results: Participants (n=3522) with documented coronary heart disease were randomised to experimental (n=1777) or control (n=1745) groups. Experimental patients received education and counseling about ACS symptoms and actions required. Patients had a mean age of 67 +/- 11 years, and 68% were male. over the 2 years of follow-up, 565 patients (16.0%) were admitted to an emergency department with ACS symptoms a total of 842 times. Neither median prehospital delay time (experimental, 2.20 versus control, 2.25 hours) nor emergency medical system use (experimental, 63.6% versus control, 66.9%) was different between groups, although experimental patients were more likely than control to call the emergency medical system if the symptoms occurred within the first 6 months following the intervention (P=0.036). Experimental patients were significantly more likely to take aspirin after symptom onset than control patients (experimental, 22.3% versus control, 10.1%, P=0.02). The intervention did not result in an increase in emergency department use (experimental, 14.6% versus control, 17.5%). Conclusions: The education and counselling intervention did not lead to reduced prehospital delay or increased ambulance use. Reducing the time from onset of ACS symptoms to arrival at the hospital continues to be a significant public health challenge. Clinical Trial Registration: clinicaltrials.gov. Identifier NCT00734760.(Circ Cardiovasc Qual Outcomes. 2009;2:525-532).